Comparing movement-related cortical potential between real and simulated movement tasks from an ecological validity perspective - Ogahara, Kakuya; Nakashima, Akira; Suzuki, Tomotaka; Sugawara, Kenichi; Yoshida, Naoshin; Hatta, Arihiro; Moriuchi, Takefumi; Higashi, Toshio (Frontiers in Human Neuroscience, 2024)
Concerns regarding the ecological validity of movement-related cortical potential (MRCP) experimental tasks that are related to motor learning have recently been growing. Therefore, we compared MRCP during real movement task (RMT) and simulated movement task (SMT) from an ecological validity perspective. The participants performed both RMT and SMT, and MRCP were measured using electroencephalogram (EEG).EEG was based on the 10-20 method, with electrodes placed in the motor cortex (C3 and C4) and supplementary motor cortex (FCz [between Fz and Cz] and Cz) areas. This experiment examined the MRCP using Bereitschaftspotential (BP) and negative slope (NS') onset times, and BP, NS', and motor potential (MP) amplitudes during the task. The results revealed that the SMT exhibited later BP and NS' onset times and smaller BP, NS', and MP amplitudes than the RMT. Furthermore, in RMT, the onset time of MRCP was delayed, and the amplitude of MRCP was smaller in the second half of the 200 times task than in the first half, whereas in SMT, there was no change in onset time and amplitude. The SMT showed a different MRCP than the RMT, suggesting that the ecological validity of the task should be fully considered when investigating the cortical activity associated with motor skill learning using MRCP. In conclusion, ecological validity of the study should be fully considered when investigating the cortical activity associated with motor skill learning using MRCP.Moreover, it is important to understand the differences between the two methods when applied clinically.